2016
DOI: 10.4103/1119-3077.175962
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different surface treatments on push-out bond strengths of fiber-reinforced posts luted with dual-cure resin cement

Abstract: Air abrasion attained higher bond strengths when FRC posts were luted to dual-cure resin cement. Additional studies should be designed with different types and parameters of laser devices to understand the effect of these devices on bond strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Comparison of air abrasion and 1.5 W power Er:YAG laser for fiber post surface treatment revealed the highest bond strength in posts treated with air abrasion [16]. However, further studies are needed to investigate the efficacy of laser surface treatment with different irradiation parameters [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of air abrasion and 1.5 W power Er:YAG laser for fiber post surface treatment revealed the highest bond strength in posts treated with air abrasion [16]. However, further studies are needed to investigate the efficacy of laser surface treatment with different irradiation parameters [16].…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of air abrasion and 1.5 W power Er:YAG laser for fiber post surface treatment revealed the highest bond strength in posts treated with air abrasion [16]. However, further studies are needed to investigate the efficacy of laser surface treatment with different irradiation parameters [16]. Another study showed that treatment of fiber post with 2780 nm Er,Cr:YSGG laser (1.5 W) increased its push-out bond strength to root dentin in the entire canal length [17].…”
Section: Introductionmentioning
confidence: 99%
“…This was followed by silane application to the post surface. The parameters used were: 10 Hz repetition rate, 150 mJ energy, 1.5 W output power, and pulse duration of 100 μs [12][13][14][15] .…”
Section: Surface Treatmentsmentioning
confidence: 99%